Comparative efficacy and safety of lock solutions for the prevention of catheter-related complications including infectious and bleeding events in adult haemodialysis patients: a systematic review and network meta-analysis. (May 2020) - Sheng, K.X.; Zhang, P.; Li, J.W.; Cheng, J.; He, Y.C.; Böhlke, M.; Chen, J.H.
Abstract: Background: Central venous catheters are used extensively as temporary or permanent vascular access for haemodialysis patients. Catheter-related bloodstream infections are the main complication of central venous catheters and increase morbidity and mortality in haemodialysis patients. Objectives: The aim was to assess the most appropriate lock solution for central venous catheters to prevent catheter-related bloodstream infections and other complications. Data sources: Medline, Embase and the Cochrane Central Register of Controlled Trials from the date of their inception to August 2018 were used as data sources. The reference lists of eligible studies and relevant reviews were also checked. Study eligibility criteria and participants: Randomized controlled trials (RCTs) comparing different lock solutions for the prevention of central venous catheter-related infectious and bleeding complications for adult dialysis patients were included. Interventions: Interventions were lock solutions for haemodialysis catheters. Methods: The primary outcomes were catheter-related bloodstream infections and bleeding events. The secondary outcomes were catheter malfunction, exit-site infection, and all-cause mortality. We estimated summary risk ratios (RRs) using pairwise and network meta-analysis. We assessed the risk of bias of individual studies with the Cochrane risk of bias tool. Results: Forty-nine trials (7020 patients) were included for this study. Compared with heparin 5000 U/mL, antibiotic locks (antibiotics with trisodium citrate (TSC), ethylenediamine tetraacetic acid (EDTA), heparin 5000 U/mL, low-dose heparin or urokinase) and ethanol locks were more effective in preventing catheter-related bloodstream infections. Antimicrobial agents plus low-dose heparin (500–2500 U/mL), TSC and low-dose heparin locks had lower risk of bleeding events than heparin 5000 U/mL. None of the lock solutions reduced rates of catheter malfunction and all-cause mortality compared with heparin 5000 U/mL. In summary, antibiotics plus low-dose heparin was ranked as the best lock solution. The overall results were not materially changed in sensitivity analyses. Conclusions: Taking into account both efficacy and safety, antibiotics plus low-dose heparin (500–2500 U/mL) may be the preferred lock solution.